Phase Change Materials: Design and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
There is increasingly intensive research for energy storage technologies development due to the enhanced energy needs of the contemporary societies. Increased global energy consumption results in the reduction in the availability of traditional energy resources, such as coal, oil and natural gas. Therefore, there is an urgent need for new systems development based on the conversion and storage of sustainable and clean energy. Phase change materials (PCMs) are one of the key components for the development of advanced sustainable solutions in renewable energy and engineering systems. In order to update the field of renewable energy and engineering systems with the use of PCMs, a Special Issue entitled “Phase Change Materials: Design and Applications” is introduced. This book gathers and reviews the collection of ten contributions (nine articles and one review), with authors from Europe, Asia and Americam accepted for publication in the aforementioned Special Issue of Applied Sciences.